I Miss Being Me: Phenomenological Effects of Deep Brain Stimulation. Issue 2 (3rd April 2017) - Gilbert, Frederic; Goddard, Eliza; Viaña, John Noel M.; Carter, Adrian; Horne, Malcolm
Abstract : The phenomenological effects of deep brain stimulation (DBS) on the self of the patient remains poorly understood and under described in the literature, despite growing evidence that a significant number of patients experience postoperative neuropsychiatric changes. To address this lack of phenomenological evidence, we conducted in-depth, semistructured interviews with 17 patients with Parkinson's disease who had undergone DBS. Exploring the subjective character specific to patients' experience of being implanted gives empirical and conceptual understanding of the potential phenomenon of DBS-induced self-estrangement. Our study concluded that (1) the more patients preoperatively felt alienated by their illness, the more they experienced postoperative self-estrangement, and (2) the notion of self-estrangement seems to exist in association with certain common qualitative characters, namely, loss of control, which reflects a deteriorative estrangement, and distorted perception of capacities, which reveals a restorative estrangement. These findings indicate that subjective self-reports help us to understand some aspects of the potential phenomenon of DBS-induced self-estrangement.